Development of an Academic Services Chatbot Based on Retrieval-Augmented Generation (RAG) - Mohammad Labib Husain; Yudi Wibisono; Ani Anisyah (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
Higher education institutions struggle to provide accurate and accessible academic information. Traditional chatbots are often limited in capability, while standard Large Language Models (LLMs) pose a significant risk of factual